Information Technology Architecture and Employee Innovation Performance in Iraqi University Libraries - Dr.Omaima Hameed Aladilee Aladilee (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: University libraries operate in dynamic knowledge environments that require technological systems capable of supporting information services and organisational activities. Specific Background: Information technology architecture, including hardware and equipment, software and databases, communications networks, and human resources, provides a framework that supports employees in performing their tasks and generating innovative ideas. Knowledge Gap: Empirical research integrating information technology architecture and employee innovation performance in the context of Iraqi university libraries remains limited. Aims: This study examines the relationship between information technology architecture and employee innovation performance in the libraries of the University of Karbala. Results: Using survey data from 87 employees and structural equation modelling analysis, the findings show a statistically significant relationship between information technology architecture and employee innovation performance (β = 0.796, p < 0.001), explaining 68.6% of the variance in innovation performance. Novelty: The study integrates multiple dimensions of information technology architecture with indicators of employee innovation performance within the organisational context of university libraries. Implications: The findings indicate that strengthening technological resources, communication networks, software systems, and staff development is associated with improved innovative work practices in knowledge institutions. Highlights: • Information Technology Architecture Dimensions Show Significant Relationships With Employee Innovative Capabilities.• Structural Equation Modelling Explains 68.6 Percent of Innovation Performance Variance in Libraries.• Technological Resources and Staff Development Support Creative Work Practices in Knowledge Institution. Keywords: Information Technology Architecture, Employee Innovation Performance, University Libraries, Information Systems Infrastructure, Organizational Innovation.